Efficient low-temperature debromination and high selectivity products recovery from brominated epoxy resin waste by subcritical water-urea treatment. (15th May 2020) - Xiu, Fu-Rong; Li, Yifan; Qi, Yingying
Graphical abstract: Highlights: We report an efficient subcritical water-urea process for treatment of BRP waste. Debromination and selective products recovery were achieved simultaneously. Debromination efficiency reached 99.92% at 300 °C. The purity of 2-bromo-phenol recovered at 200 °C reached 72.5%. The purity of phenol recovered at 250 °C reached 81.5%. Abstract: In this study, a subcritical water-urea (SubCW-urea) process was developed for the treatment of brominated epoxy resin powder (BRP) waste. The SubCW-urea process had two significant advantages: efficient low-temperature debromination and highly selective products recovery. The NH3 and CO2 released from urea in the SubCW medium had a prominent enhancement effect on the decomposition and debromination of BRP waste when the SubCW temperature was below 300 °C. The debromination efficiency of SubCW-urea treatment was significantly enhanced in comparison with that of SubCW-NH3 and single SubCW treatments. The debromination efficiency of BRP could reach 38.21%, 85.3%, and 99.92% at 200 °C, 250 °C, and 300 °C, respectively. The debromination rate constant of BRP in SubCW-urea, SubCW-NH3, and single SubCW system was 0.1363, 0.1254, and 0.0146 min −1, respectively. No brominated chemical compound could be detected in the oil phase products when the treatment temperature was higher than 250 °C. The decomposition products of BRP waste could be easily regulated by controlling the treatment temperature of SubCW-urea. 2-bromo-phenol with the purity of 72.5% could be selectively prepared from BRP by SubCW-urea process at 200 °C. The purity of the recovered phenol could reach as high as 81.5% at 250 °C. The selectivity of the products decreased greatly at 300 °C due to the secondary reactions. The SubCW-urea process has an application prospect in the safe treatment of BRP waste with the aim of high-efficiency debromination and high selectivity products recovery at low temperature.